Pengaruh Model Pembelajaran Probing Prompting Berbantuan Video Terhadap Hasil Belajar Dan Kemampuan Berpikir Kritis Peserta Didik - Rosi Pratiwi; Hikmawati Hikmawati; I Wayan Gunada (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
This research aim to examine the effect of probing prompting assisted video learning model for learning outcomes and critical thinking skill of student. This type of research is quasi experiment with untreated control group design with pretest and posttest. The research population was all students of X MIA MAN 2 Mataram. Sampling technique of this research use cluster random sampling so that there are two classes that is X MIA 1 as the experimental class and X MIA 3 as the control class. Type test used 20 choice question for learning outcomes and 5 essay for critical thinking skill. The posttest mean value for learning outcomes in experimental class and control class is 42,36 and 34,86. The posttest mean value for critical thinking skill in experimental class and control class is 54,86 and 46,08. Hypothesis testing of this research is MANOVA. The result of MANOVA test show a significant 0,004 so H0 is rejected and Ha is accepted. The conclusion of this research is there is the effect ofÃÂ  probing prompting learning model assisted video for learning outcomes and critical thinking skill of student.ÃÂ